O riso irônico na obra poética de Cruz e Sousa - Silva, Célia Marília (2012)
This work brings up a review on the poetic works of Cruz e Sousa, a nineteenth-century Brazilian poet. Laughter has been chosen as an analytical category, because it is a pertinent theme which makes possible a more accurate comprehension of the lyric content of Cruz e Sousa s poetic works. The laughter manifested in his verses is seen as a mechanism which compensates both normativeness and seriousness, as well as turns inside out whatever society establishes as being natural or an absolute truth. Amongst his poems, we will focus on the ones which express their lyric nature both through laughter and irony, since these elements serve as a means to criticize the Brazilian society in the late nineteenth-century and early twentieth-century. This study is guided by theories of laughter proposed by Minois (2003), Bakhtin (1993), Bergson (2007), as well as Adorno s (2003) and Antonio Candido s (2010) theoretical assumptions concerning lyric poetry and society